Crack propagation and crack direction changes during the hydraulic fracturing of coalbed. (July 2019) - Zhao, Yuan; Cao, Shugang; Shang, Delei; Yang, Hongwei; Yu, Yongjun; Li, Yong; Liu, Jinquan; Wang, Hui; Pan, Ruikai; Yang, Hongyun; Zhang, Bo; Tu, Huaijian
Abstract: Hydraulic fracturing is an effective treatment technology to improve reservoir permeability. In this paper, the dual effective stress was introduced into the theoretical analysis of water pressure during crack initiation, and the theoretical analysis results are about 37% more accurate than Hubbert and Willis theory based on the numerical results. Moreover, the artificial-macrocrack effects on fracturing crack propagation and direction changes have been analyzed and compared to hydraulic fracturing without the artificial-macrocrack. The water pressure required for crack initiation with the artificial-macrocracks is less than that without the artificial-macrocracks. When α ( α is defined as the angle between the artificial-macrocrack and the horizontal direction ) reached or exceeded π/4, crack growth began at the tip of the macrocrack with a higher box counting dimension than that at a lower values of α . Furthermore, a series of simulations have been conducted to obtain the point of fracturing crack direction change when α = 0. The fracturing crack starts to propagate at the artificial-macrocrack tip when λ = 0.95 (λ is defined as the ratio of horizontal stress to vertical stress), and the crack propagation direction becomes vertical when λ = 0.9625. By extracting the crack morphology from the simulation results, it was determined that the box-counting dimension, the crack perimeter, and the crack area proportion reach maximal values at λ = 0.95, λ = 0.9625 and λ = 0.975, respectively. Using image segmentation technology, the impact area proportion reached a maximum at λ = 0.9625 with a more effective treatment than at other values of λ. Finally, beddings and cracks in natural strata were taken into account for fracturing crack propagation, and beddings and cracks could guide the fracturing cracks. More microcracks could be generated along the beddings with the artificial-macrocrack effect at λ = 0.9. Case study indicated that the gas extraction achieved high production in the first 40 days, and the field data with fracturing treatment show that the average pure gas flux is about 4 times greater than that without fracturing. This research also provides a new idea to mine intact rock of construction aggregate.